Systematic Literature Review on Implementation of Environmentally Sustainable Banking: Motivation, Benefits, and Challenges - Tiwari, Ghanashyam; Sharma, Neeta Dhusia; Roy, Abhisek Saha (The Indonesian Journal of Accounting Research, 2024)
Despite the fact that implementing environmentally friendly banking encompasses several difficulties, the banking industry is now driven to do so globally. Due to the increasing depletion of natural resources and the worsening effects of climate change, the banking sector must undertake a paradigm shift toward sustainable business practices. The study aims to identify the motivational factors for the implementation of environmental sustainability in banking practices. Furthermore, this study intends to examine the barriers the banking industry faces in implementing and integrating environmental sustainability into their operations through a systematic literature review of 45 research articles published in various databases. The used database covers the period of 2015 to 2023. "Green banking" is a cutting-edge approach that incorporates environmental considerations into banking operations, loan disbursement, and investment decisions. Hence, this study thoroughly analyzes the motivations, benefits, and difficulties of green banking to promote sustainable activities. It promotes sustainable development, stakeholder value maximization, and stakeholder satisfaction, which requires a regulatory framework and stakeholder awareness and engagement. There are several challenges to adopting environmental sustainability, including a lack of understanding and guidance from the government and regulators. This study provides valuable insights for financial institutions, governments, and academics to understand green banking practices and environmental sustainability.